2017
DOI: 10.1186/s12967-017-1339-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at microRNA binding sites of Ara-C and anthracyclines-metabolic pathway genes are associated with outcome of acute myeloid leukemia patients

Abstract: BackgroundGene polymorphisms at microRNA-binding sites (poly-miRTS) may affect gene transcription and expression through miRNA regulation, which is associated with cancer susceptibility, sensitivity to chemotherapy and prognosis. This study investigated the association between poly-miRTS of Ara-C/anthracycline metabolic pathways genes and the outcome of acute myeloid leukemia (AML) in Chinese patients after Ara-C-based chemotherapy.MethodsA total of 17 poly-miRTS were selected from the SNPinfo Web Server and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Moreover, no significant effect of these SNPs on chemotherapy-related toxicities was seen. In contrast, Cao et al demonstrated an association of MRP1 SNPs with gastrointestinal toxicities after chemotherapy in a Chinese population, which we could not confirm in our study of Caucasian patients [ 26 ]. No correlation was observed regarding age, gender, ECOG performance status, FAB subtypes, bone marrow blasts at diagnosis, or baseline blood count parameters (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, no significant effect of these SNPs on chemotherapy-related toxicities was seen. In contrast, Cao et al demonstrated an association of MRP1 SNPs with gastrointestinal toxicities after chemotherapy in a Chinese population, which we could not confirm in our study of Caucasian patients [ 26 ]. No correlation was observed regarding age, gender, ECOG performance status, FAB subtypes, bone marrow blasts at diagnosis, or baseline blood count parameters (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Using the SNPinfo Web Server 20 (http://snpinfo.niehs.nih.gov/) and HaploReg, version 4.1 21 (http://pubs.broadinstitute.org/mammals/haploreg/haploreg.php), the functions of SNPs associated with EC risk were successfully predicted (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…One previous study found that this SNP was significantly associated with chemotherapy‐related toxicities in Chinese acute myeloid leukemia (AML) patients. 37 The possible underlying mechanism responsible for the observed association originated from ABCC1 rs3743527 might be the alteration of binding ability with miRNA due to its location in 3’-UTR. To date, the impact of genetic polymorphisms within ABCC2 on clinical response to MTX has only been evaluated in a few studies.…”
Section: Discussionmentioning
confidence: 99%